Intermittent chemotherapy for miliary tuberculosis in children - Anadol, Deniz; Kiper, Nural; Göçmen, Ayhan; Özçelik, Uğur (The Turkish Journal of Pediatrics, 1999)
Miliary tuberculosis is a severe manifestation of tuberculosis. Six children aged between two months and 10 years with the diagnosis of miliary tuberculosis were treated with intermittent antituberculous therapy for six, nine or 12 months. All the patients showed clearance of both clinical and radiological symptoms; there was no drug toxicity or resistance and no relapses were seen in the follow-up period ranging from nine months to nine years. Intermittent therapy is safe and effective in miliary tuberculosis and it may be an alternative therapy because of its minimal toxicity and lower cost.
Keywords: miliary tuberculosis; intermittent chemotherapy; children